Effect of Calcium and Available Phosphorus Levels on Growth Performance, Bone Characteristic and Mineral Digestibility of Broilers Fed Diets Supplemented with 1,25(OH)2D3-glycoside - Aiaowanit, Ananya; Pongmanee, Koonphol; Attamangkune, Seksom; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2022)
Two experiments were conducted to study the effect of calcium (Ca) and available phosphorus (aP) levels in broiler fed diet containing 1,25(OH)2D3-glycoside on growth performance, bone characteristics and mineral digestibility using Completely Randomized Design (CRD). Experiment 1, growth performance and bone characteristics were studied using 270 male Ross 308 broilers. All birds were randomly divided into 3 dietary treatments with different Ca: and aP levels including, T1) 0.77:0.48%, 0.69:0.43% and 0.61:0.38% in starter, grower and finisher diets, respectively), T2) 0.69:0.43%, 0.61:0.38% and 0.53:0.33% in starter, grower and finisher diets, respectively) and T3 as T2 supplemented with 1,25(OH)2D3-glycoside 100 g/ton. Each treatment consisted of 6 replicates with 15 birds each. Ca:aP ratio of all diets were kept constant at 1.6:1. Experiment 2, apparent ileal digestibility (AID) of Ca and phosphorus (P) was studied using 108 male Ross 308 broilers. All birds were randomly divided into 3 dietary treatments like Experiment 1. Each treatment consisted of 6 replicates with 6 birds each. There was no significant difference on growth performance, bone characteristics and AID of Ca and P (P>0.05). However, the finding from these studies showed that the Ca and aP level in T2 with Ca:aP ratio was 1.6:1 that had no detrimental effect on modern broilers performance when compared to T1.